2022
DOI: 10.3389/fsurg.2022.890377
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Dysfunction in Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder. Repetitive pauses in breathing during sleep cause a brief but recurrent decrease in oxygen saturation in organs and tissues (chronic intermittent tissue hypoxia). Many studies have proven a pro-inflammatory status in OSA patients. However, few reports are available on the effects of OSA on the cellular immune system, mostly focusing on single immune cell types and their subtypes. The aim of this Mini-Review is to summarize these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…While this may contribute to some variation in tonsil or adenoid immune cell proportions 18 , the effect of this underlying condition on results obtained from distal sample types in these children (nasal brushings, bronchial brushings, blood) is unclear. A recent review revealed conflicting evidence of immune cell alterations in adult and paediatric OSA, with some studies reporting an inflammatory effect while others reported normal immune responses in these patients 19 . All children in our cohort were clinically well at the time of sample collection and there was limited evidence of wheezing or respiratory infection in the week leading up to sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…While this may contribute to some variation in tonsil or adenoid immune cell proportions 18 , the effect of this underlying condition on results obtained from distal sample types in these children (nasal brushings, bronchial brushings, blood) is unclear. A recent review revealed conflicting evidence of immune cell alterations in adult and paediatric OSA, with some studies reporting an inflammatory effect while others reported normal immune responses in these patients 19 . All children in our cohort were clinically well at the time of sample collection and there was limited evidence of wheezing or respiratory infection in the week leading up to sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…14,26 In addition, abnormalities in cellular immunity have been documented in PASC; 14 OSA also has been associated with cellular immune dysfunction and therefore may be a contributing factor to the abnormal immune function in PASC. 29…”
Section: Discussionmentioning
confidence: 99%
“…Children with OSA are more likely to have cardiovascular morbidity and neurobehavioral impairment, emphasizing the urgency of early detection, diagnosis, and treatment 6 . Untreated OSA has been associated with alterations in various immune parameters, including decreased levels of certain immune cells and cytokines, making patients more prone to infectious disease 7 . OSA patients suffer from chronic sleeping deprivation, accompanied by chronic inflammation and affecting host defense abilities.…”
Section: Introductionmentioning
confidence: 99%
“…6 Untreated OSA has been associated with alterations in various immune parameters, including decreased levels of certain immune cells and cytokines, making patients more prone to infectious disease. 7 OSA patients suffer from chronic sleeping deprivation, accompanied by chronic inflammation and affecting host defense abilities. The weakened host defense abilities increase the risk of vulnerability to the viral pathogen infections, such as the influenza virus.…”
mentioning
confidence: 99%